HR Policy Development for Logistics Company in Intramuros, Manila (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2020)
The company is a fast-growing holding firm that has seen the potentials of one of the sunrise industries, which are logistics and supply chain. The company provides synchronized end-to-end supply chain solutions inside and outside the country. They have approximately 600 manpower across the country, the majority of which is in Luzon. The company has nationwide operations and has offices in Cebu, Davao, Cagayan De Oro, and General Santos City. The head office of this company is located in Intramuros, Manila. The researchers used a variety of methods to help the researchers in gathering information regarding the company, such as a face-to-face interview with the HR officers and provided questionnaires to the employees as a tool to gather data. The researchers also used online references to support ideas for the study. The researchers compared the company’s current policies with those of other companies in the same industry to find out best practices that the company may adopt. The researchers identified existing policies, such as attendance policy, equal employment opportunity, employment exit, office protocol, personnel file, confidential information, compensation and benefits, statutory benefits mandated by law, company benefits, employment process, employment status, employee safety, health work-life balance, drug-free workplace, employee engagement training, new employee orientation, transfer, promotion, performance review, practices having synergy, employee manual, anti-harassment policy, policy against retaliation, conflict of interest, anti-bribery, and code of discipline. The researchers proposed 15 policies that may be useful and helpful, as follows: Earth Hour, Data Privacy Policy, Solo Parent Leave, Bereavement Leave, Employee Referral, Seasonal Employment, Annual Sports Fest, Employee Assistance Program, Defensive Driving Seminar, Site Transfer, Reward and Recognition Policy, Open Door Policy, Fidelity to Duty, and Data Privacy Officer. Lastly, the researchers enhanced the disciplinary action of the company. Policies that are developed and enhanced by the researchers may be beneficial for the use or reference of the company.
Keywords: policy development, procedures, logistics industry